HUBUNGAN MEKANISME KOPING DENGAN STRES KERJA PERAWAT DI RSU GMIM BETHESDA TOMOHON - Mundung, Grace Jinny; Kairupan, B H Ralph; Kundre, Rina (JURNAL KEPERAWATAN, 2019)
Abstract :Stress is an epidemic that spreads throughout the world according to the World Health Organization. Stress occurs in Asian countries Survey from PPNI in 2006, around 50.9% of nurses, worked in 4 provinces in Indonesia. Objective :this research is to know the correlation between coping mechanisms with job stress in nurses at general hospital GMIM Bethesda Tomohon. Research Design : Type of this research is quantitative and using descriptive analytic research method with cross sectional approach. The sampling technique using probability sampling, stratified random sampling method and to determine the sample size, using the Slovin formula and obtained a sample of 53 respondents. Research Result : This research used the Kolmogorov-Smirnov test at a significant level of 95% which found that a significant value was 0.001. Conclusion : results of this research indicate that there is a correlation between coping mechanisms and job stress in nurses at general hospital GMIM Bethesda Tomohon. Keywords: Nurse, Coping Mechanisms, Job Stress Abstrak :Menurut World Health Organization stres merupakan epidemi yang menyebar ke seluruh dunia. Stres terjadi di negara-negara Asia. Survei dari PPNI tahun 2006, sekitar 50,9% perawat yang bekerja di 4 provinsi di Indonesia mengalami stres kerja. Tujuan : penelitian ini bertujuan untuk mengetahui hubungan mekanisme koping dengan stres kerja perawat di RSU GMIM Bethesda Tomohon. Desain penelitian : jenis penelitian kuantitatif menggunakan metode penelitian deskriptif analitik dengan pendekatan cross sectional. Teknik pengambilan sampel probability sampling metode stratified random sampling dan untuk menentukan besar sampel menggunakan rumus Slovin, didapat jumlah sampel sebanyak 53 responden. Hasil penelitian : menggunakan uji Kolmogorov-smirnov pada tingkat kemaknaaan 95% di dapat bahwa nilai signifikan adalah 0.001. Kesimpulan : hasil penelitian ini menunjukkan terdapat hubungan antara mekanisme koping dengan stres kerja perawat di RSU GMIM Bethesda Tomohon. Kata Kunci: Perawat, Mekanisme Koping, Stres Kerja